A Documentation of the Annual Poverty Indicators Survey - Carmelita N. Ericta; Jeremias Luis (Philippine Institute for Development Studies (PIDS), 2009)
In years when the Family Income and Expenditure Survey (FIES) is not conducted and when funds are available, the National Statistics Office administers the Annual Poverty Indicators Survey (APIS). The APIS has been conducted in the years 1998, 1999, 2002, 2004, 2007, and 2008. It presents the socioeconomic profile of Filipino families and other information relating to their living conditions. This document makes it possible for users to understand better the APIS, its scope, how it differs from the FIES, and the objectives of the survey, among others.
Keywords: 330; poverty; Annual Poverty Indicators Survey (APIS); bottom 30%; Armut; Sozialstatistik; Philippinen